Shared Access to Adults' Patient Portals: A Secret Shopper Exercise - Wachenheim, Deborah; Hurwitz, Isabel; Dukhanin, Vadim; Wolff, Jennifer L.; DesRoches, Catherine M. (Applied Clinical Informatics, 2024)
Background Millions of Americans manage their health care with the help of a trusted individual. Shared access to a patient's online patient portal is one tool that can assist their care partner(s) in gaining access to the patient's health information and allow for easy exchange with the patient's care team. Shared access provides care partners with a validated and secure method for accessing the patient's portal account using their own login credentials. Shared access provides extra privacy protection and control to the patient, who designates which individuals can view their record. It also reduces confusion for the care team when interacting with the care partner via the portal. Shared access is underutilized among adult patients' care partners.Objectives Investigate the process of granting or receiving shared access at multiple health care organizations in the United States to learn about barriers and facilitators experienced by patients and care partners.Methods The Shared Access Learning Collaborative undertook a “Secret Shopper” exercise. Participants attempted to give or gain shared access to another adult's portal account. After each attempt they completed a 14-question survey with a mix of open- and closed-ended questions.Results Eighteen participants attempted to grant or receive shared access a total of 24 times. Fifteen attempts were successful. Barriers to success included requiring paper forms with signatures, lack of knowledgeable staff, lack of access to technical support, and difficult-to-navigate technology. Facilitators included easy-to-navigate online processes and accessible technical help. Participants who were successful in gaining shared access reported feeling more informed and able to engage in shared decision-making.Conclusion The outcomes of our secret shopper exercise underscore the importance of collaboration aimed at learning from diverse encounters and disseminating the best practices. This is essential to address technical, informational, and organizational obstacles that may impede the widespread and accessible adoption of shared access.
Keywords: patient portal; caregiver; informal caregiver; family caregiver; patient engagement; proxy access; shared access